2023
DOI: 10.3390/ijms24065560
|View full text |Cite
|
Sign up to set email alerts
|

OsαCA1 Affects Photosynthesis, Yield Potential, and Water Use Efficiency in Rice

Abstract: Plant growth and crop yield are essentially determined by photosynthesis when considering carbon dioxide (CO2) availability. CO2 diffusion inside a leaf is one of the factors that dictate the CO2 concentrations in chloroplasts. Carbonic anhydrases (CAs) are zinc-containing enzymes that interconvert CO2 and bicarbonate ions (HCO3−), which, consequently, affect CO2 diffusion and thus play a fundamental role in all photosynthetic organisms. Recently, the great progress in the research in this field has immensely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Its application in crop engineering, i.e., integrating CAs involved in C4 or crassulacean acid metabolism or algal carbon-concentrating mechanisms (in which various CAs are also involved) into cultivars for boosting agricultural yields has been recently demonstrated to be feasible (Findinier and Grossman AR, 2023;Förster et al, 2023) and might be of crucial relevance in a planet with >8 billion inhabitants. The field is in its infancy, but the recent breakthrough mentioned previously as well as other similar research studies (He et al, 2023) showed that both αand β-CAs of rice (Oryza sativa) are essential for photosynthesis, providing the possibility for engineering plants for high-yielding crops.…”
Section: Discussionmentioning
confidence: 99%
“…Its application in crop engineering, i.e., integrating CAs involved in C4 or crassulacean acid metabolism or algal carbon-concentrating mechanisms (in which various CAs are also involved) into cultivars for boosting agricultural yields has been recently demonstrated to be feasible (Findinier and Grossman AR, 2023;Förster et al, 2023) and might be of crucial relevance in a planet with >8 billion inhabitants. The field is in its infancy, but the recent breakthrough mentioned previously as well as other similar research studies (He et al, 2023) showed that both αand β-CAs of rice (Oryza sativa) are essential for photosynthesis, providing the possibility for engineering plants for high-yielding crops.…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis is the fundamental process behind plant growth and development, as it supplies the necessary materials and energy for their progress [ 13 ]. Chlorophyll is a key light-absorbing molecule that provides valuable information about the structure, conformation, and function of the photosynthetic apparatus through its fluorescence [ 14 ].…”
Section: Introductionmentioning
confidence: 99%